Graduate Studies and Multiprofessional Residency in Healthcare at HC-UFG: the production of Social Work - Denise Carmen Andrade Neves; Tereza Cristina Pires Favaro; Carla Ágda Gonçalves (Revista Katálysis, 2017)
The purpose of this paper is to discuss the production of Social Work in Multiprofessional Residency in Health; particularly,the study of Final Term Papers (TCCs) submitted by residents that have completed the Multiprofessional Residency in Health Program of the Clinical Hospital of the Federal University of Goiás/EBSERH between 2012 and 2016.